Control of shell colour changes in the lobster, Panulirus cygnus - Wade, N.; Smith, Roy; Degnan, B.; Hall, M. (The Company of Biologists Ltd., 2008)
The transition from juvenile to adult in the Australian western rock lobster, Panulirus cygnus (George), is preceded by a mass migration from inshore nursery reefs to offshore breeding grounds. Associated with this migration is a moult which results in the animals that are due to migrate undergoing characteristic colour change from deep red to pale pink, known as the `white' phase, which is believed to be triggered by environmental factors. To investigate this phenomenon, the colour change of wild-caught animals was measured over two separate years in response to two important modifiers of crustacean shell colour, dietary carotenoid and background substrate colour. Changes in shell colour during this colour transition period were influenced more greatly by other factors independent of diet or background substrate and no mass colour change was induced during this time. Shell colour measurement and carotenoid quantification confirmed the presence of animals similar to wild-caught `whites', regardless of the treatment. From these experimental observations we infer that the `white' phase of the western rock lobster is not triggered by dietary modification or in response to background substrate. We propose that this transition is under the regulation of an ontogenetic program activated at a specific moult, which induces presently unidentified molecular changes linked to shell colour production. This unique colour transition may have evolved to provide protective camouflage during migration, and serves as an excellent model to study the genetic mechanisms underlying crustacean shell colouration. These data also provide insight into the changes in carotenoid levels induced by environmental factors, and the ability to modify crustacean shell colour in aquaculture.